2019
DOI: 10.1038/s41386-019-0323-x
|View full text |Cite
|
Sign up to set email alerts
|

An amylin analogue attenuates alcohol-related behaviours in various animal models of alcohol use disorder

Abstract: Recent findings have identified salmon calcitonin (sCT), an amylin receptor agonist and analogue of endogenous amylin, as a potential regulator of alcohol-induced activation of the mesolimbic dopamine system and alcohol consumption. Providing that the role of amylin signalling in alcohol-related behaviours remains unknown, the present experiments investigate the effect of sCT on these behaviours and the mechanisms involved. We showed that repeated sCT administration decreased alcohol and food intake in outbred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 60 publications
4
36
2
Order By: Relevance
“…Therefore, the locomotor differences noted in the present locomotion experiments could be associated with altered RAMP levels; the lack of data thereof can be considered as a limitation, and future studies are warranted. Although differential expression of the calcitonin receptor gene is detected in the NAc of high compared with low alcoholconsuming rats chronically exposed to alcohol (Kalafateli et al 2019a), the lack of effect on the protein levels of this receptor in the present could be a result of chronic alcohol exposure in rats, which is not the case in the present conditions in mice. Additionally, previous studies have showed differences in amylin-mediated behaviours between the subregions of the NAc (Baldo and Kelley 2001;Mietlicki-Baase et al 2015b).…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Therefore, the locomotor differences noted in the present locomotion experiments could be associated with altered RAMP levels; the lack of data thereof can be considered as a limitation, and future studies are warranted. Although differential expression of the calcitonin receptor gene is detected in the NAc of high compared with low alcoholconsuming rats chronically exposed to alcohol (Kalafateli et al 2019a), the lack of effect on the protein levels of this receptor in the present could be a result of chronic alcohol exposure in rats, which is not the case in the present conditions in mice. Additionally, previous studies have showed differences in amylin-mediated behaviours between the subregions of the NAc (Baldo and Kelley 2001;Mietlicki-Baase et al 2015b).…”
Section: Discussioncontrasting
confidence: 66%
“…The agonist was administered 30 min prior to alcohol administration in the experimental setup, where alcohol was administered the same day with sCT. This dose of sCT was used, as we have previously established that this dose attenuates alcohol-mediated behaviours in rodents (Kalafateli et al 2019a ; Kalafateli et al 2019b ). Moreover, this sCT dose, at least acutely, does not affect blood alcohol concentration (Kalafateli et al 2019b ), rendering the possibility of pharmacokinetic interaction between the two drugs less likely.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also characterized fully all components of the AmyR in the mPFC and CeA. Previous research has demonstrated expression of a subset of AmyR components in these nuclei (Kalafateli et al., 2019), but here we expand upon these earlier data by investigating both subtypes of CTR and all three types of RAMP , in addition to the impact of access to fat on expression of these components. Our data indicate that all CTR and RAMP subtypes are expressed in the mPFC and CeA.…”
Section: Discussionmentioning
confidence: 99%
“…The CTRs and RAMPs can dimerize in different combinations to form AmyRs of varying degrees of sensitivity and selectivity to amylin (Christopoulos et al., 1999; Hay, Christopoulos, Christopoulos, & Sexton, 2004; Muff, Buhlmann, Fischer, & Born, 1999). One paper showed that some components of the AmyR are expressed in PFC and CeA (Kalafateli et al., 2019) but did not fully characterize expression of all potential AmyR components within these nuclei. Thus, the particular components of the AmyR that are expressed in these sites are not completely resolved.…”
Section: Introductionmentioning
confidence: 99%